The Etika Bisnis Dalam Islam Pada Perilaku Pedagang di Jalan Sekumpul Martapura Kalimantan Selatan - Diany, Adista Anjar (DAS Institute, 2025)
Uneven economic development results in many people who have to struggle and not a few experience shortages in the fulfillment of life, forcing them to do various bad deeds so that many business practices in Islamic society are far from even in accordance with Islamic values. The purpose of this study is to determine the application of business ethics and Islamic business ethics in the behavior of traders on Jalan Sekumpul Martapura South Kalimantan. The type of research is qualitative research using purposive sampling data collection techniques or sampling data sources with certain considerations. The number of respondents in this study were 45 respondents who were traders or who sold in the Jalan Sekumpul Martapura area. The results showed that the indicators of business ethics in general and Islam have been applied well by the traders. The culture of the Banjar people in the Banjarmasin area is an interesting finding to research, so it is recommended that the next research or other researchers research about it.